Predicting Phonological Awareness: The Roles of Mind-Wandering and Executive Attention - Yao, Cheng; Jun, Hu; Dai, Guang-Song (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the predictive relationships between mind-wandering, executive attention, and phonological awareness. Methodology: A cross-sectional design was utilized, encompassing 300 participants recruited from a large urban university. Participants underwent assessments using the Comprehensive Test of Phonological Processing, Second Edition (CTOPP-2) for phonological awareness, the Mind-Wandering Questionnaire (MWQ) for mind-wandering, and the Attention Network Test (ANT) for executive attention. Data were analyzed through multiple linear regression using SPSS Version 27, assessing the predictive power of mind-wandering and executive attention on phonological awareness. Findings: The regression analysis demonstrated that mind-wandering and executive attention significantly predict phonological awareness, explaining 35% of its variance (R² = 0.35). Mind-wandering was found to have a negative impact on phonological awareness, with a standardized beta coefficient (β) of -0.22 and a p-value of